Estimation of Composite Laminate Ply Angles Using an Inverse Bayesian Approach Based on Surrogate Models. (May 2022) - Franz, M.; Pfingst, S.; Zimmermann, M.; Wartzack, S.
Abstract: A digital twin (DT) relies on a detailed, virtual representation of a physical product. Since uncertainties and deviations can lead to significant changes in the functionality and quality of products, they should be considered in the DT. However, valuable product properties are often hidden and thus difficult to integrate into a DT. In this work, a Bayesian inverse approach based on surrogate models is applied to infer hidden composite laminate ply angles from strain measurements. The approach is able to find the true values even for ill-posed problems and shows good results up to 6 plies.